Constraints in Implementing Adolescent Friendly Health Services in Bangladesh: Health System Aspects from the Service Providers (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Adolescent Friendly Health Services (AFHS) aim to provide accessible, confidential and comprehensive care to adolescents, yet service gaps and implementation challenges persist in Bangladesh.Objective: To identify health system-related constraints in implementing AFHS from the perspective of service providers.Methods: This multi-center cross-sectional study conducted from January to December 2018 assessed constraints in implementing Adolescent Friendly Health Services (AFHS) at four Adolescent Friendly Health Corners (AFHC) in Dhaka and Gazipur, Bangladesh, including two NGO and two government facilities. Participants included health facility managers (n=5), healthcare providers (n=8), outreach workers (n=12), and supporting staff (n=5), purposively selected. Data were collected using WHO-adapted semi-structured questionnaires on socio-demographics and service delivery.Results: The findings revealed that HFMs oversaw administrative and clinical activities, with 80% reporting inconvenient service hours. All HFMs provided reproductive, nutritional and mental health services; however, there were gaps in HIV counseling (20%) and STI/RTI diagnosis (80%). The majority of reproductive health services were provided by healthcare providers, mostly counselors and paramedics, with only 12.5% offering STI/RTI diagnosis or 0% counseling for HIV-positive adolescents. Outreach workers and peer educators actively included adolescents in community programs, with 83-92% trained in referral procedures. Supporting staff were primarily responsible for facility operations and acknowledged discomfort with some teenage groups (20%) as well as insufficient referral training (0%). Common recommendations included increasing waiting areas, expanding educational/entertainment offerings and strengthening referral systems.Conclusion: This study identifies gaps in HIV care, STI/RTI management, staff training, resources and privacy within AFHS. Strengthening capacity, ensuring resource availability, and engaging adolescents are essential to enhance service quality and accessibility in both NGO and government facilities in Bangladesh.JAFMC Bangladesh, Vol 21, No 2 (December) 2025:59-66